FAKTOR-FAKTOR YANG MEMPENGARUHI KONSUMEN DALAM MEMILIH PERUMAHAN (STUDI KASUS: PERUMAHAN VILLA CITRA DAN VILLA BUANA GARDENIA) - Zamzami Zamzami; Abdullah Abdullah; Hafnidar A. Rani (Prodi Magister Teknik Sipil Unsyiah, 2018)
The city of Banda Aceh, apart from being the administrative center of Aceh's administration, is also a center of economic, educational and trade activities, so that economic growth and population are growing rapidly. Consumer preferences in choosing housing varies greatly, because every individual has different desires in choosing the desired housing. The purpose of this study is to determine the preferences of consumers in choosing and determine the desired housing. Based on the result of correlation analysis, that the quality factor/character of social environment (Xe6) correlation between consumer preferences in choosing Villa Citra housing equal to R = 0,358 shows